Pengaruh Stress Kerja, Disiplin Kerja, dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan UD. Podo Seneng - Pratiwi, Ajeng Fara Harum; Listyani, Indah; Wardhani, Rike Kusuma (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the influence of work stress, work discipline, and work environment on employee productivity at UD. Podo Seneng. A quantitative approach was employed using survey methods through questionnaires, interviews, and observations. The sampling technique applied was saturated sampling, involving the entire population of 40 employees. Data analysis included validity and reliability tests, classical assumption tests, and multiple linear regression analysis supported by t-tests, F-tests, and the coefficient of determination (R²). The results show that, partially, work stress has a negative but insignificant effect on productivity. In contrast, work discipline and work environment have a positive and significant effect on productivity. Simultaneously, the three variables significantly influence employee productivity, contributing 49.7% to the variance. These findings indicate that strengthening work discipline and creating a conducive work environment are dominant factors in improving productivity, while the effect of work stress remains inconsistent and requires further investigation in different organizational contexts.